Pembuatan Media Pembelajaran Animasi Berbasis Powtoon pada Mata Pelajaran Estimasi Biaya Konstruksi - Naufal Vadillah; Ari Syaiful Rahman Arifin; M. Giatman; Muvi Yandra (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
This study uses classroom action research with a model developed by Kurt Lewin (1944) including planning, action or action, observation, and reflection. Problems in the Construction Cost Estimation subject are inadequate learning media and students' understanding of the Construction Cost Estimation material is not yet optimal. Based on the validity of the research instrument experts obtained an assessment of 90% categorized as very feasible, the validity of the media expert was 0.80 and the validity of the material expert was 0.72 categorized as valid. The practicality of the teacher is 0.74 and the student is 0.70 which is categorized as practical. The results of the first cycle with observations of teacher activity obtained an average of 1.61 percent 40% and 2.39 percentage 60%, and cycle II obtained an average of 3.33 percentage 47% and 3.78 percentage 53%. The results of the first cycle with observations of student learning activities obtained an average of 7.67 percent 47% and 8.70 percent 53%, and cycle II obtained an average of 10.79 percent 53% and 13.29 percent 55%. The average results of the pre-test and post-test in cycle I were 82.07 and 87.24, and in cycle II was 87.41 and 93.28. The t-test with paired sample t-test obtained (sig. 2-tailed) 0.000 <0.05 with Ho rejected and Ha accepted, so it can be concluded that there was a significant increase in student learning outcomes with Powtoon learning media.